OPTIMALISASI LETAK TOWER CRANE TERHADAP WAKTU SIKLUS PADA PROYEK Y - Satrio Mahardhika; Afrizal Nursin (Politeknik Negeri Jakarta, 2022)
In a construction project, there are various kinds of very complex activities. Therefore, heavy equipment, especially Tower Cranes is used to assist the work on the construction project. The layout of the Tower Crane must be considered because the optimal location of the Tower Crane will result in efficient cycle times and productivity values. Thus, the purpose of this study is to obtain the factors that must be considered in determining the location of the Tower Crane, and the location of the Tower Crane that is the most optimal and efficient in the project under review. In this study, 3 scenarios will be conducted according to the feasible area and the location of the Tower Crane closing to the building structure in under construction. Scenario 1, is the existing location in project Y. In scenario 2, the setting out of location of Tower Crane 1 is moved to coordinates (152.10; 43.30) and Tower Crane 2 is moved to coordinates (41.36; 29, 38). Scenario 3, the location of Tower Crane 2 is set to coordinates (36.60; 21.38). Analysis and comparison of the cycle time and productivity of Tower Crane were conducted on this paper. Result of the lowest total cycle time of 17277.32 minutes was obtained in scenario 3, 1048.53 minutes faster than the existing condition (scenario 1). In addition, the highest productivity value was obtained in scenario 3, with 5078.00 kg/hour for Tower Crane 1 and 5559.73 kg/hour for Tower Crane 2. From analysis performed for (3) three scenarios, Scenario 3 was also considered as the most optimal scenario based on several consideration factors in determining the location of the Tower Crane. Keywords: Cycle Time, Optimization, Productivity, Scenario, Tower Crane.